Down-regulation of miR-340-5p promoted osteogenic differentiation through regulation of runt-related transcription factor-2 (RUNX2) in MC3T3-E1 cells - Xiaochen Wang; Yaochuan Mi; Wei He; Xiaona Hu; Shuo Yang; Lu Zhao; Yanyang Zhang; Binhong Wen (Taylor & Francis, 2021)
Diabetic osteoporosis (DOP) is a chronic complication of diabetes in the skeletal system. High level of miR-340-5p may be harmful to the bone formation. In this study, the DOP model of rats was successfully established via streptozotocin (STZ) and ovariectomy (OVX) treatment. It was manifested by reduced body weight, insulin level, alkaline phosphatase (ALP) activity, and osteocalcin (OCN) and collagen-I expressions, as well as increased concentration of fasting blood glucose. Moreover, we found that miR-340-5p expression was increased while runt-related transcription factor-2 (RUNX2) was decreased in femurs. Furthermore, the effects of miR-340-5p on osteogenic differentiation (OD) in high glucose (HG)-treated MC3T3-E1 cells were explored. Exposure to OD and HG contributed to elevated miR-340-5p level. Inhibition of miR-340-5p enhanced ALP level, calcium deposition, and OCN, collagen-I and RUNX2 levels. On the contrary, miR-340-5p overexpression reversed these promotional effects. Luciferase assay indicated that RUNX2 may be a target gene of miR-340-5p. Moreover, RUNX2 deficiency decreased miR-340-5p inhibition-induced ALP activity, calcium accumulation and OCN, collagen-I, RUNX2 levels. In short, the above findings revealed that inhibition of miR-340-5p facilitated osteogenic differentiation through regulating RUNX2 in MC3TC-E1 cells, which provided targeted therapeutic strategies for the treatment of DOP.
Keywords: Biochemistry; Cell Biology; Genetics; Molecular Biology; Physiology; Chemical Sciences not elsewhere classified; Biological Sciences not elsewhere classified; Developmental Biology; Cancer